The transplant patient : biological, psychiatric, and ethical issues in organ transplantation - Trzepacz, Paula T.; DiMartini, Andrea F. (Cambridge University Press, 2000)
This book reviews the psychosocial, psychiatric and ethical aspects of organ transplantation. Uniquely interdisciplinary and authoritative, and drawing on the pioneering work of the Pittsburgh transplant team, it will appeal to a wide audience including those who select, support and advise transplant patients, and the clinicians performing the procedures.